HOW ARE BUSINESSES ADOPTING CIRCULAR PRACTICES - EMPIRICAL STUDY ON THE CASE OF GEORGIA AND SELECTED EASTERN EUROPEAN COUNTRIES - Tsotne Zhghenti; Vakhtang Chkareuli; Manuel Rios de Haro; Valentin Molina Moreno; Dzintra Atstaja (Agora International Journal of Economical Sciences (AIJES), 2023)
The shift towards circular practices requires a variety of supportive actions from different parties, such as education from academic institutions, institutional support from government and policymakers, and financial aid. Our research aims to provide data on the adoption of circular practices in Georgia and selected Eastern European countries. The findings of the research summarize the trends of adoption of circular practices among firms in different economies.In today's rapidly changing business environment, companies are under increasing pressure to reduce their environmental impact and embrace sustainable practices. Circular economy is seen as a promising solution to these challenges, as it shifts the focus from linear models of production and consumption to a closed-loop system where waste is reduced and resources are conserved.The concept of circular economy has gained significant traction in recent years, as companies seek to reduce their environmental impact and achieve long-term sustainability. By adopting circular practices, companies can reduce the cost of goods sold, improve resource efficiency, and promote a cleaner environment. However, the adoption of circular practices requires a significant change in organizational culture, which can be challenging for many businesses.Our research aims to provide practical information for policymakers and stakeholders from the private sector on the adoption of circular practices in Georgia and selected Eastern European countries. The results of the research will provide valuable insights into the trends of adoption of circular practices among firms in different economies and highlight the benefits of embracing circular economy.In conclusion, the transition to circular practices is a highly sought-after trend for businesses seeking to reduce their cost of goods sold, promote sustainability, and benefit from a cleaner environment. The adoption of circular practices requires a significant change in organizational culture, which can be challenging for many businesses. Our research aims to provide practical information for policymakers and stakeholders from the private sector on the adoption of circular practices in Georgia and selected Eastern European countries and summarize the trends of adoption of circular practices among firms in different economies.
Keywords: 330